Destination choices during internal temporary migration: Evidence from northern Bangladesh - Md. Sohel Rana; Amy Faye (PLoS ONE, 2026)
While migration to urban areas is often associated with higher wage opportunities, it remains unclear why many rural poor prefer rural destinations, particularly for temporary migration. We investigate this in northern rural Bangladesh, where temporary migration is common, by analyzing both the determinants of rural versus urban temporary migration and their income effects. We examine temporary migrants’ destination choices, accounting for their self-selection into migration, and address endogeneity when estimating the income effects of these choices. Despite recent findings that perceived income gains tend to be higher from rural destinations, our findings show that rural destinations are not necessarily better than urban ones at increasing actual total household income. In fact, remittances from rural-bound temporary migration are lower than those from urban-bound migration. However, our results also suggest that rural-bound migration is not primarily driven by remittance maximization. Instead, constrained by household obligations, temporary migrants often prefer rural destinations because they offer greater income-to-cost ratio, permit continued engagement in origin-based labor activities, and hence facilitate household risk diversification while reducing time away from home.